2014
DOI: 10.1186/s12866-014-0221-7
|View full text |Cite
|
Sign up to set email alerts
|

The heat sensitive factor (HSF) of Yersinia ruckeriis produced by an alkyl sulphatase involved in sodium dodecyl sulphate (SDS) degradation but not in virulence

Abstract: Background: The heat sensitive factor (HSF) of the fish pathogen Yersinia ruckeri was previously identified as an unusual band on SDS-PAGE. According to this, Y. ruckeri strains were classified in HSF + and HSF − in terms of the presence/absence of the factor. Experiments carried out by injection challenge with HSF + strains caused high mortalities in rainbow trout. In contrast, HSF − strains did not cause mortality. In conclusion, HSF appeared to be a relevant virulence factor in Y. ruckeri. Results: We repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Some Y. ruckeri strains are flagellated and consequently exhibit variable motility with peritrichously arranged flagella (Tobback et al, 2007). Y. ruckeri can be recovered from the internal organs of infected fish, and then cultured on bacteriological media such as Tryptone Soya Agar , Nutrient Agar (Navais et al, 2014), Brain Heart Infusion Agar (Arias et al, 2007), Columbia Blood Agar (Gibello et al, 2004) and McConkey Agar (Akhlaghi and Sharifi Yazdi, 2008;Gibello et al, 1999). After 24-48 hours of incubation, the bacterium forms smooth, circular, shiny colonies (Busch, 1978 catalase and negative for indole, hydrogen sulfide, oxidase, cytochrom, phosphatase, urease, phenylalanine deaminase (Ewing et al, 1978).…”
Section: General Characteristicsmentioning
confidence: 99%
“…Some Y. ruckeri strains are flagellated and consequently exhibit variable motility with peritrichously arranged flagella (Tobback et al, 2007). Y. ruckeri can be recovered from the internal organs of infected fish, and then cultured on bacteriological media such as Tryptone Soya Agar , Nutrient Agar (Navais et al, 2014), Brain Heart Infusion Agar (Arias et al, 2007), Columbia Blood Agar (Gibello et al, 2004) and McConkey Agar (Akhlaghi and Sharifi Yazdi, 2008;Gibello et al, 1999). After 24-48 hours of incubation, the bacterium forms smooth, circular, shiny colonies (Busch, 1978 catalase and negative for indole, hydrogen sulfide, oxidase, cytochrom, phosphatase, urease, phenylalanine deaminase (Ewing et al, 1978).…”
Section: General Characteristicsmentioning
confidence: 99%
“…Heat sensitive factor (HSF) produced by the alkylsulphatase enzyme YraS has been proposed as a virulence factor [ 50 ], and a differential culture medium, using Coomassie Brilliant Blue has been developed to identify strains that carry this factor [ 51 ]. However, recent findings have contradicted these results and suggested that HSF might not be required for Y. ruckeri virulence [ 52 ]. Similarly, the cdsAB operon was initially identified through in vitro expression technology [ 49 ] and has been shown to be required for uptake of L-cysteine by the bacterium [ 53 ].…”
Section: Virulence Factorsmentioning
confidence: 99%
“…The third group includes enzymes with the metallo-β-lactamase-like domain in the N-terminus and SCP-2-like domain in C-terminus. Six sulfatases with different substrate specificities have been characterized to date: SdsA, YraS, and YjcS with activity toward sodium dodecyl sulfate (SDS) ( Davison et al, 1992 ; Liang et al, 2014 ; Navais et al, 2014 ), SdsAP and SdsA1 with activity toward primary sulfate esters including sodium dodecyl sulfate ( Hagelueken et al, 2006 ; Long et al, 2011 ; Schober et al, 2011 ) and Pisa1 with activity toward secondary alkyl sulfates ( Schober et al, 2011 ). Enzymes from this group differ in the mechanism of action and could cleave either S-O or C-O bond causing the retention or inversion of the product alcohol, which could be verified using chiral or labeled substrates.…”
Section: Introductionmentioning
confidence: 99%